Application Of Nitrogen And Boron On Growth And Nutrient Contents Of Okra (Abelmoschus Esculentus L.) Grown On Soil (Journal of the Asiatic Society of Bangladesh, Science, 2015)
A pot experiment was conducted in the net house of the Department of Soil, Water and Environment, University of Dhaka to find out the interactive effects of nitrogen (0, 30, 60 and 120 kg/ha) and boron (0, 0.5, 1 and 2 kg/ha) fertilizers on the growth and nutrient contents of okra (Abelmoschus esculentus L.). The increase in height of okra was significant (p